The Prophet Muhammad Saw the Wisdom of the Prophet’s Miracles - Malinda, Mutia Dara; Djamduri, Dewi Suryani (Letiges, 2021)
The Prophet Muhammad SAW is a role model of all Muslims. The miracles from Allah, the Almighty to gave him is a proof for his Prophetic. As Muslims we must believed and take lesson from it, because those all provisions of Allah, the Almighty has given. This reseach is a qualitative reaseach and aims to get more known about the lesson of the miracles of Prophet. It is used document research to get the aims and with study looks at the verses of the Holy Qur’an, Hadiths, some previous study and books. The miracles of Prophet Muhammad SAW that have from Allah, the Almighty always have the reasons and from it this articles can find the answer of lesson in life and as guided in Allah’s path. The result of this research are expected to helps all Muslims more better understand and deepen what the Prophet Muhammad conveyed as the Messenger of Allah.